Use of Processed Sugarcane Bagasse Ash in Concrete as Partial Replacement of Cement: Mechanical and Durability Properties - Shazim Ali Memon; Usman Javed; Muhammad Izhar Shah; Asad Hanif (Buildings, 2022)
Using biomass waste as supplementary cementing material (SCM) in concrete has attracted researchers’ attention for efficient waste utilization and reducing cement demand. Sugarcane bagasse ash (SCBA) is one such example of biomass waste. It is an agricultural waste obtained when sugarcane bagasse from the sugar industry is used for power generation and disposed of in open-air dumping sites. Its waste disposal causes the generation of particulate matter, degrading air quality. In this study, the effect of processed SCBA as SCM in concrete has been investigated. The processing of the SCBA involved the removal of fibrous and carbon-containing particles by sieving followed by grinding. The SCBA was ground for 45 min until the surface area was comparable to that of cement and was then used for further characterization and incorporation into concrete. The 45 min grinding time resulted in 2.92 times higher pozzolanic reactivity of the SCBA. The SCBA was incorporated by replacing cement in different weight fractions (10%, 20%, 30%, 40%) in concrete. Test results showed that the concrete workability increased with SCBA incorporation, whereas the resulting concrete density was reduced. The results of the mechanical properties, including compressive sstrength and hardened density, were enhanced upon the cement replacement by SCBA. Concrete containing 30% SCBA can be used for structural applications as its 28 days compressive strength was 21 MPa, which complies with ACI 318-16 specifications. Concrete resistance against scaling and leaching due to adverse effects of sulfuric and hydrochloric acid considerably increased with SCBA addition and was due to microstructure densification by secondary hydrates formation as lower portlandite content was detected by thermogravimetric analysis. Hence, SCBA processing increases its reactivity, as reflected by the improved mechanical properties and greater durability of SCBA-incorporated concrete.